1987
DOI: 10.1136/adc.62.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of daytime enuresis using alarm procedures: a randomly controlled trial.

Abstract: SUMMARY Forty four children with daytime wetting were included in a randomly controlled trial of two alarm devices, a contingent one that sounded when wetting occurred and a non-contingent one that went off from time to time unrelated to wetting events. A quota allocation system ensured comparability between treatment groups. Two thirds responded to an alarm by becoming dry. The non-contingent alarm produced as good a response as the contingent one and is recommended for routine use in children with diurnal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 7 publications
0
27
1
3
Order By: Relevance
“…The attainment of dryness after the age of 10 years increased the risk for behavioral problems -independently of the primary or secondary status [9]. Equally, the group of day-wetting children as a whole were more psychiatrically disturbed than controls [10] and than nocturnal enuretics [4,5] in parental and teacher questionnaires, as well as by psychiatric assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The attainment of dryness after the age of 10 years increased the risk for behavioral problems -independently of the primary or secondary status [9]. Equally, the group of day-wetting children as a whole were more psychiatrically disturbed than controls [10] and than nocturnal enuretics [4,5] in parental and teacher questionnaires, as well as by psychiatric assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In einer frĂĽhen Studie, die nicht den jetzigen kinderpsychiatrischen Standards entspricht, zeigten 30% der tags einnäs-senden Kinder eine Verhaltensaufällig-keit [13], in einer anderen Studie zeigten 25% der Kinder eindeutige und weitere 14% mögliche emotionale Störungen [21]. In der eigenen Studie erfĂĽllten 53% aller tags einnässenden Kinder die Kriterien In einer neueren pädiatrischen Studie von 418 Kinder im Alter von 5-17 Jahren wurden die tags einnässenden Kinder als sturer, oppositoneller und verheimlichender beschrieben als die nächt-lichen Enuretiker [24].…”
Section: Klinische Studienunclassified
“…12 In majority of studies the intervention was given for 12 weeks. 18,19 The accepted treatment period for nocturnal enuresis was reported by Forsythe to be 12-16 weeks. 20 In the present study it was found that reduction in mean number of wet night started from 8 weeks of intervention and best results were seen after 20 weeks.…”
mentioning
confidence: 99%